Organizational and training factors that promote team science: A qualitative analysis and application of theory to the National Institutes of Health's BIRCWH career development program. Issue 2 (8th February 2017) - Guise, Jeanne-Marie; Winter, Susan; Fiore, Stephen M.; Regensteiner, Judith G.; Nagel, Joan
Abstract : Introduction: Research organizations face challenges in creating infrastructures that cultivates and sustains interdisciplinary team science. The objective of this paper is to identify structural elements of organizations and training that promote team science. Methods: We qualitatively analyzed the National Institutes of Health's Building Interdisciplinary Research Careers in Women's Health, K12 using organizational psychology and team science theories to identify organizational design factors for successful team science and training. Principal Results: Seven key design elements support team science: (1) semiformal meta-organizational structure, (2) shared context and goals, (3) formal evaluation processes, (4) meetings to promote communication, (5) role clarity in mentoring, (6) building interpersonal competencies among faculty and trainees, and (7) designing promotion and tenure and other organizational processes to support interdisciplinary team science. Conclusion: This application of theory to a long-standing and successful program provides important foundational elements for programs and institutions to consider in promoting team science.